2023
DOI: 10.1007/s40801-023-00352-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Medication Adherence Among Older People Admitted to Hospital: A Descriptive Study

Abstract: Background Poor medication adherence is prevalent among older people. To optimize therapeutic outcomes, it is crucial to understand the underlying causes and perceptions. Objective We aimed to investigate the extent of self-reported medication adherence and associated factors among older people admitted to hospital. Methods Individuals living at home aged ≥ 75 years with an emergency admission at a university hospital between September 2018 and September 2021 were included. Participants answered the Medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…The personal factors related to drug non-adherence are divided to two categories of intentional non-adherence including self-drug discontinuance and unintentional non-adherence including problems such as forgetfulness, visual impairment, and inability to move, among which forgetting is a very important cause of poor medication adherence [ 8 ]. Poor medication adherence has been reported in 26–59% in older adults, depending on the population and methods used to assess drug adherence [ 9 ]. Also a study on 24,000 Iranian elderly patients showed that 62% of them forgot to take their medications [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The personal factors related to drug non-adherence are divided to two categories of intentional non-adherence including self-drug discontinuance and unintentional non-adherence including problems such as forgetfulness, visual impairment, and inability to move, among which forgetting is a very important cause of poor medication adherence [ 8 ]. Poor medication adherence has been reported in 26–59% in older adults, depending on the population and methods used to assess drug adherence [ 9 ]. Also a study on 24,000 Iranian elderly patients showed that 62% of them forgot to take their medications [ 10 ].…”
Section: Introductionmentioning
confidence: 99%